2016
DOI: 10.1155/2016/4081357
|View full text |Cite
|
Sign up to set email alerts
|

Response of Boron and Light on Morph-Physiology and Pod Yield of Two Peanut Varieties

Abstract: Boron is an important micronutrient that enhances vegetative growth and yield of crops, like peanut. Light also plays an important role in pegging of peanut. There has been little information regarding the application of boron and light in peanut in Bangladesh. Therefore, a field experiment was conducted to study the response of boron and light on morph-physiology and pod yield of two peanut varieties. Treatments considered two peanut varieties,namely, Dhaka-1 and BARI Chinabadam-8, three levels of boron (B),n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The positive effect of increasing foliar spray of boron application on number of pods and seed of peanut may be due to its role in cell elongation and saving flowering and fruit regulation (Zhang, 2001 andsingh et al, 2009), furthermore it had a positive role on improved the pollination (Kaisher et al, 2010). Boron increase number of branches and pods, pods and seed weight, pod, seed and oil yield in peanuts, similar findings also were recorded by Helmy & shaban (2008), Kabir et al (2013), Helmy & Ramadan (2014), Naiknware et al (2015), Quamruzzaman et al (2016), Chirwa et al (2017), Hirpara et al (2017) and Quamruzzaman et al (2018). Furthermore, concerning the positive effect of boron application onsugar beet EL-sherif, 2016) and Mekdad & Rady (2016) reported that increasing foliar spray with boron increased significantly the productivity of sugar beet, while Mekdad (2015 b) illustrated that increasing foliar spraying with micronutrients mixture levels (Fe, Mn, Zn, Cu, B and Mo) increased significantly the productivity of sesame crop.…”
Section: Effect Of Foliar Spraying With Boron Concentrationssupporting
confidence: 82%
See 1 more Smart Citation
“…The positive effect of increasing foliar spray of boron application on number of pods and seed of peanut may be due to its role in cell elongation and saving flowering and fruit regulation (Zhang, 2001 andsingh et al, 2009), furthermore it had a positive role on improved the pollination (Kaisher et al, 2010). Boron increase number of branches and pods, pods and seed weight, pod, seed and oil yield in peanuts, similar findings also were recorded by Helmy & shaban (2008), Kabir et al (2013), Helmy & Ramadan (2014), Naiknware et al (2015), Quamruzzaman et al (2016), Chirwa et al (2017), Hirpara et al (2017) and Quamruzzaman et al (2018). Furthermore, concerning the positive effect of boron application onsugar beet EL-sherif, 2016) and Mekdad & Rady (2016) reported that increasing foliar spray with boron increased significantly the productivity of sugar beet, while Mekdad (2015 b) illustrated that increasing foliar spraying with micronutrients mixture levels (Fe, Mn, Zn, Cu, B and Mo) increased significantly the productivity of sesame crop.…”
Section: Effect Of Foliar Spraying With Boron Concentrationssupporting
confidence: 82%
“…These results were collaborated with Kabir et al (2013). Naiknware et al (2015), Quamruzzaman et al (2016), Chirwa et al (2017), Hirpara et al (2017) and Hirpara et al (2018). so, the objective of this investigation is to study the effect of different levels of phosphorus on soil fertilization and foliar spray with boron application on yield and quality of peanut cultivation under dry region conditions (Egypt) over two seasons.…”
mentioning
confidence: 99%
“…It also influences the ability to retain flower and fruit setting in peanuts (Zhang 2001;Quamruzzaman et al 2017c). As a result, boron would increase the pod yield of peanuts (Quamruzzaman et al 2016a). Kabir et al (2013) stated that boron is responsible for producing healthier seeds in peanut.…”
Section: Introductionmentioning
confidence: 99%
“…Boron has also influenced the ability to retain flower and fruit setting in peanut hence increase pods number (Quamruzzaman et al, 2018b). Quamruzzaman et al (2016) also reported pod yields and germination increased with boron application of 2 kg ha -1 and accelerated flowering 4-5 days compared to control. Boron has a positive effect on vegetative growth and peanut germination.…”
Section: Discussionmentioning
confidence: 81%